2016
DOI: 10.1186/s12882-016-0272-0
|View full text |Cite
|
Sign up to set email alerts
|

Risk prediction to inform surveillance of chronic kidney disease in the US Healthcare Safety Net: a cohort study

Abstract: BackgroundThe capacity of electronic health record (EHR) data to guide targeted surveillance in chronic kidney disease (CKD) is unclear. We sought to leverage EHR data for predicting risk of progressing from CKD to end-stage renal disease (ESRD) to help inform surveillance of CKD among vulnerable patients from the healthcare safety-net.MethodsWe conducted a retrospective cohort study of adults (n = 28,779) with CKD who received care within 2 regional safety-net health systems during 1996–2009 in the Western Un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…These are available from the authors upon request. c The study by Xie [ 27 ] and Maziarz [ 29 ] includes the same patient population. Part of this population is included in Maziarz et al .…”
Section: Resultsmentioning
confidence: 99%
“…These are available from the authors upon request. c The study by Xie [ 27 ] and Maziarz [ 29 ] includes the same patient population. Part of this population is included in Maziarz et al .…”
Section: Resultsmentioning
confidence: 99%
“…It was generally observed that regardless of the model used, the predicted outcome included measurement of risk towards ESKD which were defined as [ 41 , 43 , 44 , 48 50 , 53 , 56 60 , 64 , 69 , 70 , 72 ]:…”
Section: Resultsmentioning
confidence: 99%
“…There were very few studies that had predicted outcomes such as progression from an earlier stage to a more severe stage of CKD, for example from stage 1 to stages 3 or 4 [ 54 , 56 ], and other predicted endpoints of stated percentage decline in eGFR levels [ 9 , 41 ]. Depending on the quality of the available dataset [ 59 , 60 ], the predicted outcome could also be combined with other variables such death, comorbidities, the type of dialysis and the time of diagnosis [ 46 , 59 , 68 ]. Some examples of outcomes that integrated these additional variables include, predicting the chances of future KRT at the time of CKD diagnosis [ 70 ]; a ≥ 50% decline in the eGFR from baseline [ 50 ] or an eGFR decline ≥30% from baseline [ 41 ]; the 5-year risk of KRT in CKD stage 3 and 4 [ 56 ]; the mortality and progression to ESKD over five years [ 65 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In cardiac surgical settings, CKD-patients are reported to have short life expectancy with renal dysfunction severity and are often associated with other medical problems compared to those without CKD [3,4]. Cardiac, pulmonary, metabolic, and hematological complications have a major effect on outcome after cardiac surgery [5,6] Our main aim was to investigate the association between stratum of renal impairment with the outcome of morbidity and mortality during peri-operative period of isolated mitral valve replacement; and to identify further the degree of renal failure at time of prosthetic mitral valve replacement going to affect the outcomes of surgery.…”
Section: Introductionmentioning
confidence: 99%